Geneza i zawartość Programu nauczania-uczenia się infotechniki - Wawrzyniak, Krzysztof; Ubermanowicz, Stanisław (Fundacja Wolnego i Otwartego Oprogramowania, 2014)
- Artykuł uzasadniający potrzebę zmian w nauczaniu programowania i konstruowania, ukazujący cele ogólne, proponowane treści i założone efekty merytoryczne zajęć pozalekcyjnych w formie kół zainteresowań infotechnicznych.

- The article justifies the need of change in the teaching of programming and design; it presents general goals, offered content and assumed effects of extracurricular classes in the form of circles of interest on info-technology.
Origin and content of the Program of teaching and learning of info-technology
Keywords: program nauczania; curriculum; koła zainteresowań; circles of interest; cele zajęć; goals of the class; treści zajęć; class content; efekty zajęć; class effects; programowanie; programming; kompetencje; competences; umiejętności; skills; reforma edukacji; reform of education; strategia; strategy; SWOI